Up from the Depths: The Cultural Appropriation of Godzilla in 1970s American Animation and Comics - C. Scott Maravilla (Humanities)
The approach taken by Marvel and Hanna-Barbera to adapting Godzilla for a young American audience is a form of cultural appropriation. Cultural appropriation involves removing the subject from its cultural context. In this case, Marvel and Hanna-Barbera removed the character from its origin, where it emerged as a consequence of the atomic bomb. Gojira is first a scourge of Japan and later its savior against invasion from cosmic forces and nefarious kaiju. Godzilla is changed into what is ultimately a sanitized version of imperial inventory. The properties of the 1970s Godzilla, however, were not wholly negative. Indeed, they laid the foundation for an American rediscovery of the original Gojira film and its sequels, which have since been released in their original versions. This article will examine how Marvel Comics and Hanna-Barbera cartoons culturally appropriated Godzilla for American children, but how this also led to an appreciation of the Japanese films.